Computations of stress intensity factors for semi-elliptical cracks with high aspect ratios by using the tetrahedral finite element (fully automated parametric study). (June 2016) - Okada, Hiroshi; Koya, Hirohito; Kawai, Hiroshi; Li, Yinsheng; Osakabe, Kazuya
Highlights: The stress intensity factors of semi-elliptical cracks with high aspect ratios are evaluated. The SIFs of the semi-elliptical cracks in a complex structure are also presented. Automated parametric studies on crack geometries and load conditions were performed. A software system for the automated parametric studies is presented. Abstract: The stress intensity factor (SIF) solutions of semi-elliptical cracks with high aspect ratios in plate and thick wall cylinder have been investigated under various assumed stress distributions. The authors have developed an automated analysis procedure to perform parametric studies on crack shapes and loading conditions. It consists of programs to perform automatic mesh generation, analysis execution including assignments of boundary conditions and SIF evaluations by VCCM (virtual crack closure-integral method). It was also found that SIF solutions for the thick wall cylinder and for the complex structure could be estimated by those for the flat plate.